Progressive muscle relaxation as a Non Pharmacological Intervention For Mild Insomnia in adolescents - Helen, Millya; Mariyana, Rina (REAL in Nursing Journal, 2025)
Introduction: Sleep disorders in adolescents vary, but some studies suggest quite a high number. Around 39% of teenagers reported experiencing insomnia or difficulty sleeping. sleep. Another study stated that up to 73.4% of adolescents experience sleep disorders. Aim: evaluating the effects of progressive muscle relaxation training (PMRE) applied to patients in improving sleep quality in adolescentsMethod: The design of this research isPre-Eksperiment Intack Group Comparison. In this study there is one group but divided into two, namely half the group for the experiment (treated) and half for the control group. The sampling technique in this study was carried out by adolescents. Determination of the sample in this study was by purposive random sampling technique, which amounted to 20 people, namely 10 experimental people and 10 control people in adolescents who experience insomnia who have met the inclusion criteria and exclusion criteria. Sample criteria Inclusion criteria: adolescents aged 11-13 years, have complaints of insomnia, do not receive pharmacological therapy, do not experience significant psychological trauma, depression, withdraw, Not consuming alcohol.Findings: The average level of difficulty sleeping in female adolescents in the control group was (2.60), meaning the level of difficulty sleeping was mild (95% CI: 1.37-2.43), with a standard deviation of 0.516.Conclusion and recommendation:  In line with these findings, it has been determinedthat PMRE improves sleep quality in adolescents. It is recommended that education about PMRE be provided and that the exercises be taught.Keywords: sleep quality, progressive muscle relaxation exercises, adolescents